Methods for the Determination of Aflatoxins and Ochratoxin A in Medicinal Plant Raw Materials (Review) - U. V. Ivanova; I. V. Gravel (Разработка и регистрация лекарственных средств, 2024)
Introduction. Aflatoxins and ochratoxin A are secondary metabolites of microscopic mold fungi. They seriously threaten human and animal health. These toxins are carcinogenic, teratogenic, hepatotoxic, nephrotoxic substances. International Agency for Research on Cancer (IARC) has classified them as class IA and IIB carcinogens. The maximum permissible concentrations of aflatoxins and ochratoxin A in the Russian Federation are currently regulated only in food products according to the Technical Regulation of the Customs Union 021 "On Food Safety". The content of aflatoxins and ochratoxin A in medicinal plant raw materials is not regulated in any way. Harmful environmental and biological conditions such as temperature, humidity, air quality, insects and others during post-harvest handling can lead to contamination of medicinal raw materials with aflatoxins and ochratoxin A. Therefore, the detection of these toxins is one of the problems of raw materials quality control.Text. The present review summarizes the following methods of sample purification, used at the sample preparation stage: solid-phase extraction, immunoaffin column and QuEChERS. This review also summarizes the following modern analysis methods for the identification of aflatoxin and ochratoxin A in medicinal plant raw materials: thin-layer chromatography, liquid chromatography, gas chromatography and screening methods.Conclusion. The QuEChERS method has been identified as the most popular method for preparing samples for analysis. It is based on solid phase extraction technology. This method combines the variability of approaches to sample purification and allows people to study a wider range of toxins. The high-performance liquid chromatography method has been identified as the most popular method for qualitative and quantitative analysis. It has high selectivity, multicomponent analysis and low detection limits.